Spatial Analysis of Gravity Anomaly Over Maar Area of Lamongan Volcanic Field - Nur Aziz, Khafidh; Jamilatusolikhah, Jamilatusolikhah; Agasti Rini, Dini; Larasati, Yanuri; Bian Itsna Ashfa, Al Ashfiya (Jurnal Sains Dasar, 2021)
<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="IN">Lamongan Volcano located<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US"> in<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="IN">, East Java<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">has basaltic cinder or spatter cones and maars.<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="IN">The presence of maar and cinder cones indicates active volcanic activity at their time<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">.<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: IN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="IN">We used secondary gravity data from GGMplu<span style="font-size: 9.0pt; line-height: 115%; font-family: 'Times New Roman',serif; mso-fareast-font-family: FangSong; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">s. The result of residual anomaly map shows that Maar which is located on the NW of Lamongan Volcano shows a lineament pattern with Lamongan Volcano which is trending northwest-southeast and maar indicates a normal fault.